The frazzled principal's wellness plan : reclaiming time, managing stress, and creating a healthy lifestyle - Queen, J. Allen; Queen, Patsy S. (Corwin Press, Inc, a Sage Publications Company, 2005)
Manage your stress and priorities so you can be the productive, creative headteacher you were meant to be! This wellness guide for today's busy headteachers, school leaders, advisors, and administrators has been custom crafted by the authors of The Frazzled Teacher's Wellness Plan to address the stresses of managing workplace environments, juggling time and competing priorities, learning to delegate, balancing personal and professional agendas, and creating win-win situations. Special features of this stress reducer and life enhancer include: Checklists for identifying and managing personal and professional stressors; Illustrated guides to Desk Yoga and other physical activities; Strategies for immediate and long-term stress reduction; Case examples, reviews, references, cartoons and more.